Foreword: Companions on the Edge of Iceland - McGillivray, Andrew (Association for the Advancement of Scandinavian Studies in Canada (AASSC), 2019)
The recent publication of Wayward Heroes, translated by Philip Roughton, marks a significant event for world literature, the first direct translation from Icelandic to English of Halldór Laxness’s masterpiece novel Gerpla. It is also a landmark event that a special volume of Scandinavian-Canadian Studies is now dedicated to criticism related to the epic novel, its formidable author, and the medieval literature from which the novel draws inspiration. Both demonstrate the continuing importance and influence of the medieval Icelandic sagas and of the works of Halldór Laxness, who notably won the Nobel Prize for Literature in 1955. https://scancan.net/pdf/mcgillivray_1_26.pdf